Exercise Training for Persons with Alzheimer's Disease and Caregivers: A Review of Dyadic Exercise Interventions. Issue 4 (4th July 2017) - Lamotte, Guillaume; Shah, Raj C.; Lazarov, Orly; Corcos, Daniel M.
ABSTRACT: Alzheimer's disease (AD) is the most common form of dementia and the prevalence will increase dramatically in the next decades. Although exercise has shown benefits for people with dementia due to AD as well as their caregivers, the impact of a dyadic exercise intervention including both groups as study participants remains to be determined. The authors review the current clinical evidence for dyadic exercise interventions, which are exercise regimens applied to both the person with dementia and the caregiver. A total of 4 controlled trials were reviewed. This review shows that dyadic exercise interventions are feasible and may produce a positive effect on functional independence and caregiver burden. However, there was insufficient evidence to support a benefit of dyadic exercise intervention on cognitive performance and on behavioral and neuropsychiatric symptoms in participants with dementia due to AD. A dyadic exercise intervention improves functional independence and caregiver burden. However, there is a need for well-designed randomized controlled clinical trials to confirm these benefits and to investigate several important points such as the effects of a dyadic exercise intervention on cognitive and noncognitive outcomes of AD, the optimal intensity of exercise training, and the cost effectiveness of such a program.